A rare cause of upper extremity deep venous thrombosis: Paget Schroetter syndrome - Erdem, Fatih; Keyik, Bahar; Çağlar, Bahadır; Serin, Süha; Bülbül, Erdoğan (Journal of Surgery and Medicine, 2021)
Paget-Schroetter syndrome is a rare clinical entity, which is characterized by the thrombosis of the axillary and/or subclavian vein resulting from the activation of the coagulation cascade due to vigorous and repetitive activity of the arm and the external compression related microtrauma to the venous intima. The first imaging modality for diagnosis should be color Doppler ultrasonography. Thrombolysis and surgical decompression of the thoracic outlet are focused on relieving the external compression of the veins. In this case report, we aimed to present the greyscale ultrasonography and dynamic Doppler ultrasonography findings of a patient with upper extremity deep venous thrombosis.